Ss Inventory Policy with Variable Delivery Time - Freeman, Raoul J. (Management Science, 1957)
In this paper we study the question of determining an Ss inventory policy in the presence of delivery time being a random variable. Otherwise the usual conditions of the problem are retained (demand is considered a random variable, etc.). We will use the basic work of Whitin (Whitin, Thomson M. 1953. The Theory of Inventory Management. Princeton University Press, Princeton.), as a starting point, and develop our analysis as an extension of his exposition (where delivery time is taken as being constant). It will be our purpose to derive formulas for the determination of the order size and of the reordering point.